From Structure Topology To Chemical Composition. XIX. Titanium Silicates: Revision of the Crystal Structure and Chemical Formula of Bafertisite, Ba2Fe2+4Ti2(Si2O7)2O2(OH)2F2, A Group-II TS-Block Mineral - F. Cámara; E. Sokolova; Y. A. Abdu; L. A. Pautov (The Canadian Mineralogist, 2016)
The crystal structure and chemical formula of bafertisite, Ba2Fe2+4Ti2(Si2O7)2O2(OH)2F2, have been revised. Three samples of bafertisite were studied using electron-microprobe analysis, Mössbauer spectroscopy, IR and Raman spectroscopy, and single-crystal X-ray diffraction. These samples are from (1) the Bayan Obo REE deposit, Inner Mongolia, China (holotype); (2) the Gremyakha-Vyrmes alkaline complex, Kola Peninsula, Russia; and (3) the Darai-Pioz alkaline massif, Tajikistan. Bafertisite is a TS-block mineral of Group II, Ti = 2 apfu (atoms per formula unit) per (Si2O7)2 (Sokolova 2006). Bafertisite is triclinic, CEmbedded Image, a 10.677(6), b 13.767(7), c 11.737(5) Å, α 90.12(1), β 112.28(4), γ 90.02(1)°, V 1596(3) Å3 (unit-cell parameters are for bafertisite from Kola, sample 2). Chemical analysis was done by electron microprobe, the H2O content was calculated from the crystal-structure solution and refinement, and the occurrence of Fe2+ and lack of Fe3+ were confirmed by Mössbauer spectroscopy. The empirical formulae were calculated on the basis of 20 (O + F) anions, with (OH + F) = 4 apfu, and they are of the form AP2MO4MH2(Si2O7)2(XO)4(XP)2, Z = 4: (1) (Ba1.89K0.03)Σ1.92(Fe2+3.33Mn0.47Mg0.11)Σ3.91(Ti1.86Nb0.07Zr0.02Mg0.05)Σ2(Si2.05O7)2O2[(OH)1.82F0.18]Σ2F2; (2) (Ba1.82Sr0.02K0.02)Σ1.86(Fe2+3.24Mn0.57Al0.06Mg0.03Ca0.01Zr0.01Zn0.01Na0.02)Σ3.95(Ti1.96Nb0.03Zr0.01)Σ2(Si2.05O7)2O2[(OH)1.59F0.41]Σ2F2; and (3) (Ba1.90K0.02)Σ1.92(Fe2+2.23Mn1.61Mg0.02Zr0.04Zn0.03)Σ3.93(Ti1.90Nb0.09Zr0.01)Σ2(Si2.03O7)2O2[(OH)1.75F0.25]Σ2F2. The crystal structures of (1), (2), and (3) were solved and refined from twinned crystals to R1 = 2.90, 2.46, and 2.74% on the basis of 4538, 4685, and 4692 unique reflections (|F| > 4σ|F|) and can be described as a combination of a TS (Titanium Silicate) block and an I (Intermediate) block. The TS block consists of HOH sheets (H-heteropolyhedral, O-octahedral). The topology of the TS block is as in Group II of the Ti disilicates: Ti + Nb = 2 apfu per (Si2O7)2 (as defined by Sokolova 2006). ...